AN EMPIRICAL STUDY OF TOTAL QUALITY MANAGEMENT ACCOUNTING IN HIGHER EDUCATION: STUDENTS AS CUSTOMERS PERSPECTIVE - Kakkar, Palak (International Journal of Research -GRANTHAALAYAH, 2017)
With increased globalisation and competitiveness in the markets, the firms are in consistent search for new methods to satisfy their customers. The concept of TQM renders useful insight to achieve the said objective. Moreover, the concept is multi-disciplinary and is well suited to the Indian concept as well. Higher Education is an important sector that needs to cater to the need of quality education in the wake of plethora of options available to the students worldwide and also to satisfy the Accredition and assessment needs by agencies like NAAC. Thus, an attempt has been made to study the impact of Total Quality Management accounting in the Higher Education Sector. The paper has been divided into seven parts. While the first and second part deals with the introduction and conceptual framework respectively, the third part focuses on the various concepts of research methodology. The results of the empirical study have been reported in the fourth part. The fifth part deals with the suggestions for the policy makers followed by the research gaps so identified. The last part deals with the conclusion.